The Roast Tradition (se'i/nu) and Acute Respiratory Infection in Infants - Anita Restu Korbaffo; Budi Prasetyo; Oedojo Soedirham (Humanistic Network for Science and Technology (HNST), 2018)
The se’i / nu tradition is one tradition that is still maintained by the local community on the island of Timor, where the process of postpartum care of mothers and newborn babies traditionally involves smoking up to 40 days or 3 months using charcoal / embers. (The smoking process involves requiring the new mother and her newborn baby to sit or lay above embers from biomass fuel inside a traditional house). The purpose of this study was to investigate the association of the smoking tradition (se’i / nu) with the incidence of acute respiratory infections in infants at the Eban district health center in North Central Timor. The type of research was analytical. The design used was an observational study. The sampling technique in this study used the total population. The sample size was 42 people. The dependent variable was the incidence of acute respiratory infection, and the independent variable was the smoking tradition (se’I / nu). The results showed that there is a correlation between the smoking tradition (se’i / nu) and the incidence of acute respiratory infection (ARI) in infants at the Eban clinic P = 0.016 (P<α). Keywords: Roast tradition, Acute respiratory infection, Infants